Dim prospects for bright light. - Corley, A.-M (IEEE spectrum)
Using ultrashort light rays to print tiny features on integrated circuits has long been a dream of chipmakers, but suppliers of the necessary tools have been dashing that dream for a decade. The sources remain too weak to print more than a handful of wafers per hour, and critical parts still lack funding. This paper discusses the problems to be encountered in utilizing a new small ultrabright extreme ultraviolet (EUV) light source for the EUV lithography industry. This paper also discusses nanoUV's new EUV light source. EUV is a euphemism for soft X-rays, things that everybody in Silicon Valley knows are devilishly hard to make and focus. What ever it is called, the radiation is attractive because its waves are around 13.5 nanometers - about as small as the features in the next generation of chips - so using them avoids the current need to print features for smaller than the wavelengths of light used to do it. The new light source that nanoUV invented consists of two plasmas - a very hot, tiny one surrounded by a cylindrical one. One big problem with such short rays, though, is that they can get absorbed by pretty much everything, including air and glass. The EUV light source combines too many new ideas with too few demonstrations of its reliability and reproducibility to attract ideal customers.